The biomechanics of blocking - Vint, P.
In the article by Peter Vint I will comment on various aspects of movement mechanics as they pertain to blocking. I will also provide some concepts (see tables below) that can integrate into several blocking drills which should increase the effectiveness of the movement, and allow for greater task specific movement enhancement over a longer period of the training year.